Nature and Empire in Ottoman Egypt An Environmental History - Mikhail, Alan (Studies in Environment and History, 2011)
"In the first ever environmental history of Ottoman Egypt, Alan Mikhail brings to life the complex relationships between Egyptians, their rural world along the Nile, and the Ottoman Empire. This detailed account of irrigation, grain cultivation, the movement of wood, disease, and labor challenges many longstanding ideas in both Ottoman and Egyptian history while at the same time demonstrating how environmental history offers new ways of thinking about the Middle East. This path braking book should be read by all those with interests in the Middle East, the Ottoman Empire, Egypt, environmental history, and early modern history."--Provided by publisher